2017
DOI: 10.2136/sssaj2017.02.0067
|View full text |Cite
|
Sign up to set email alerts
|

Soils on Historic Charcoal Hearths: Terminology and Chemical Properties

Abstract: Historic charcoal hearth remains provide a unique archive of the long-term interaction between biochar, soil development, and plant growth. Charcoal as raw material was crucial for production of iron in iron works, and hence numerous charcoal hearths can be found in the forests near historic iron works in Europe and in the eastern united States. Charcoal hearths are round to elliptical forms often around 10 m in diameter and consist of several-decimeter-thick layers that contain charcoal fragments, ash, and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…Hardy et al (2016) did not find such a large difference between hearth and reference soils at several hearth sites in Wallonia, like other authors did in other locations (e.g., Mikan and Abrams, 1996;Criscuoli et al, 2014). Hirsch et al (2017) found even a lower N content in hearth soils in Connecticut. However, an increase of N is consistent with the accumulation of uncharred SOM often found in hearth soils (Borchard et al, 2014;Kerré et al, 2016;Mastrolonardo et al, 2018).…”
Section: Contribution Of Charcoal To Soil Organic Carbon Contentsupporting
confidence: 47%
See 2 more Smart Citations
“…Hardy et al (2016) did not find such a large difference between hearth and reference soils at several hearth sites in Wallonia, like other authors did in other locations (e.g., Mikan and Abrams, 1996;Criscuoli et al, 2014). Hirsch et al (2017) found even a lower N content in hearth soils in Connecticut. However, an increase of N is consistent with the accumulation of uncharred SOM often found in hearth soils (Borchard et al, 2014;Kerré et al, 2016;Mastrolonardo et al, 2018).…”
Section: Contribution Of Charcoal To Soil Organic Carbon Contentsupporting
confidence: 47%
“…This latter included a Bw 1 and a Bw 2 horizon. Soil of RCHs showed a uniform Auh horizon, i.e., a mineral horizon enriched in charcoal and organic matter (FAO, 2006;Hirsch et al, 2017) thicker than 20 cm. Therefore, we further divided the charcoal enriched topsoil in a top part (A 1 layer), 20 cm thick, and a bottom part (A 2 layer), so allowing a direct meaningful comparison between topsoil (20 cm; A 1 layer) in the RCH and reference plots.…”
Section: Soil Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences in RCH densities between flat and sloped terrain are most likely a result of differences in hearth site usage. The morphology and stratigraphy of most RCH platforms on slopes indicate multiple uses of the sites (Hirsch et al, ; Raab et al, ; Stolz, Sebastian, & Grunert, ), whereas single‐use hearth sites are characteristic of RCHs in sandy flatland areas in Brandenburg (Hirsch, Schneider, Bauriegel, Raab, & Raab, ; Raab et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have characterized the effects of RCHs on plant colonization (Mikan and Abrams, 1995), growth (Buras et al, 2015;Criscuoli et al, 2017;Kerrè et al, 2017), and cover composition (Krause and Möseler, 1993;Carrari et al, 2016). Several recent studies also deliberately address the architecture and properties of the soils on such sites (Borchard et al, 2014;Criscuoli et al, 2014;Hardy et al, 2016;Hirsch et al, 2017;Mastrolonardo et al, 2018), mainly with a focus on soil chemistry. The physical and soil hydraulic characteristics of RCH soils have received relatively little attention so far.…”
Section: Introductionmentioning
confidence: 99%